(untitled) (Research, Society and Development, 2024)
Introduction: Baker’s cyst, also known as popliteal cyst, is an osteomuscular condition that develops in association with other inflammatory and degenerative diseases, resulting in significant pain. Objectives: The aim of this study was to evaluate the clinical, epidemiological and pathophysiological aspects of Baker’s cyst, building on knowledge based on case reports and knowledge from the literature. Materials and Methods: This is an integrative literature review on the general clinical characteristics of Baker’s cyst. The PICO strategy was used to develop the guiding question. In addition, the descriptors "Baker’s cyst"; "Popliteal cyst"; "Treatment" were cross-referenced in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (VHL) databases. Results and Discussion: The articles showed that the occurrence of Baker’s cyst is associated with degenerative and inflammatory joint diseases, and is more prevalent in individuals over the age of 40. The pathophysiological mechanisms for its development were also discussed, as well as the main clinical manifestations and diagnostic methods. Conclusion: Baker’s cyst is a benign condition that presents with joint pain, swelling and limited movement. Diagnosis is eminently clinical and complemented by imaging tests. Treatment encompasses analgesia measures that can progress to surgical procedures, depending on the severity of the case.